On opial type inequalities with nonlocal conditions and applications - Bougoffa, Lazhar; Jamal Ibrahim, Daoud (Department of Mathematics, Kyungpook National University, South Korea, 2011)
The purpose of this note is to give Opial type inequalities with nonlocal conditions. Also, a reverse of the original inequality with y(a) = y(b) = 0 is derived. We apply these inequalities to second-order dierential equations with nonlocal conditions to derive several necessary conditions for the existence of solutions.